1995
DOI: 10.1055/s-2007-1013765
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Grafting after Failed Coronary Angioplasty: Risk Factors and Long-Term Results

Abstract: In this case-control study we investigated the preoperative risk factors and long-term results in patients undergoing emergency coronary artery bypass grafting (CABG) after failed percutaneous transluminal coronary angioplasty (PTCA). From January 1990 to March 1993, 56 emergency CABGs (Group A) were performed in patients from 7 different cardiology centres--six of these located outside our hospital within a radius of 19 km-1 h to 114 h (phi 7.3 h) after failed PTCA. No special stand-by was given and patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Several studies have reported worse outcomes for patients undergoing CABG after acute PCI associated with complications, [11][12][13][14][15] but few studies have assessed outcomes after CABG procedures after initially successful and uneventful PCI. 16 -18 Moreover, no study has explicitly excluded patients undergoing primary PCI for acute myocardial infarction, where patients are more likely to be treated solely for their culprit lesion, with incomplete revascularization.…”
Section: Clinical Perspective On P 467mentioning
confidence: 99%
“…Several studies have reported worse outcomes for patients undergoing CABG after acute PCI associated with complications, [11][12][13][14][15] but few studies have assessed outcomes after CABG procedures after initially successful and uneventful PCI. 16 -18 Moreover, no study has explicitly excluded patients undergoing primary PCI for acute myocardial infarction, where patients are more likely to be treated solely for their culprit lesion, with incomplete revascularization.…”
Section: Clinical Perspective On P 467mentioning
confidence: 99%
“…With the advent of intracoronary stenting, there has been a decrease in the need for emergency CABG ranging between 0.4% and 2% (49,305,(338)(339)(340)(341)(342). Not surprisingly, emergency CABG surgery for a patient with an occluded or dissected coronary artery is associated with a higher mortality than elective surgery (146,(343)(344)(345)(346)(347). Emergency procedures are also associated with high rates of perioperative infarction and less frequent use of arterial conduits.…”
Section: Role Of Onsite Cardiac Surgical Back-upmentioning
confidence: 99%
“…Rescue abciximab was effective in stabilizing patients experiencing PCI-related ischemic complications such as abrupt vessel closure and compared favorably to historical experience [16,17]. However, the rescue group had a higher incidence of postprocedure MI and a poorer longterm outcome mainly driven by the need for repeat revascularization.…”
Section: Discussionmentioning
confidence: 86%